Noninvasive prenatal diagnosis of Huntington disease: detection of the paternally inherited expanded CAG repeat in maternal plasma. (5th April 2015) - van den Oever, Jessica M. E.; Bijlsma, Emilia K.; Feenstra, Ilse; Muntjewerff, Nienke; Mathijssen, Inge B.; Bakker, Egbert; van Belzen, Martine J.; Boon, Elles M. J.; Chitty, Lyn S.; Bianchi, Diana W.
Abstract Objective With a shift towards noninvasive testing, we have explored and validated the use of noninvasive prenatal diagnosis (NIPD) for Huntington disease (HD). Methods Fifteen couples have been included, assessing a total of n = 20 pregnancies. Fetal paternally inherited CAG repeat length was determined in total cell‐free DNA from maternal plasma using a direct approach by PCR and subsequent fragment analysis. Results All fetal HD (n = 7) and intermediate (n = 3) CAG repeats could be detected in maternal plasma. Detection of repeats in the normal range (n = 10) was successful in n = 5 cases where the paternal repeat size could be distinguished from maternal repeat patterns after fragment analysis. In all other cases (n = 5), the paternal peaks coincided with the maternal peak pattern. All NIPD results were concordant with results from routine diagnostics on fetal genomic DNA from chorionic villi. Conclusion In this validation study, we demonstrated that all fetuses at risk for HD could be identified noninvasively in maternal plasma. Additionally, we have confirmed results from previously described case reports that NIPD for HD can be performed using a direct approach by PCR. For future diagnostics, parental CAG profiles can be used to predict the success rate for NIPD prior to testing. © 2015 John Wiley & Sons, Ltd.